2015
DOI: 10.1515/pjvs-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating peptide-27 (PACAP-27) is co-stored with galanin, substance P and corticotropin releasing factor (CRF) in intrapancreatic ganglia of the sheep

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide existing in two variant forms (of either 27 or 38 residues), widely present in numerous organs and evoking multiple effects both in the central and peripheral nervous systems. The present study was undertaken to evaluate the distribution pattern of PACAP-27 expression in the ovine pancreas. Using double immunohistochemical stainings co-localizations of PACAP-27 with galanin, SP or CRF were studied in intrapancreatic neurons. In intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The presence of PACAP in the GI tract has been described in various mammal species, including humans [7,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. However, it should be emphasized that the distribution of PACAP differs between different parts of the GI tract in the same species and shows interspecies differences.…”
Section: Localization Of Pacap In the Gastrointestinal Tract In Individual Species Of Mammalsmentioning
confidence: 99%
“…The presence of PACAP in the GI tract has been described in various mammal species, including humans [7,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. However, it should be emphasized that the distribution of PACAP differs between different parts of the GI tract in the same species and shows interspecies differences.…”
Section: Localization Of Pacap In the Gastrointestinal Tract In Individual Species Of Mammalsmentioning
confidence: 99%
“…Catecholaminergic sympathetic neurons often co-express neuropeptide Y (NPY) [ 18 , 19 ], whereas ACh co-localizes with vasoactive intestinal peptide (VIP) [ 20 , 21 ]. Alongside, peptides like pituitary adenylate cyclase-activating peptide (PACAP) and enkephalin and somatostatin have been described in the sympathetic nervous system [ 22 , 23 ]. In this review, we will focus on the peptidergic co-transmitters of peripheral sympathetic and parasympathetic nerves, especially in the musculoskeletal system.…”
Section: Biology Of Sympathetic Neuropeptides and Their Receptorsmentioning
confidence: 99%
“…PACAP is co-localized with VIP in the neurons of the rat pancreas (Hannibal and Fahrenkrug, 2000). PACAP is also co-localized with galanin, SP, and corticotrophin-releasing factor (CRF) in the intrapancreatic ganglia of the sheep pancreas (Arciszewski et al, 2015). Moreover, both galanin and NPY can be observed in intrapancreatic ganglia of the bovine pancreas (Furuzawa et al, 1996; Myojin et al, 2000; Adeghate et al, 2001), with galanin being more frequently observed than NPY (Myojin et al, 2000).…”
Section: Neurotransmitters Of Intrapancreatic Gangliamentioning
confidence: 99%